Classification Of Papaya Leaf Diseases Using The Convolutional Neural Network Method With The Mobilenetv3 Architecture - Komang Bagus Sadewa Netra; Putu Indah Ciptayani; Luh Gede Putri Suardani (Jurnal Media Computer Science, 2026)
This study aims to develop a classification system for papaya leaf diseases based on digital image processing using the Convolutional Neural Network (CNN) method with the MobileNetV3 architecture. The background of this research is the manual process of identifying papaya leaf diseases by farmers, which is often inefficient and prone to misdiagnosis. The research method adopts a software engineering approach using the Agile development model, allowing iterative and flexible system development. The dataset consists of papaya leaf images categorized into three classes: curl, ringspot, and healthy, obtained from field observations and secondary datasets. The data were processed through preprocessing stages before being used to train the CNN model. The results indicate that the best model was achieved using a learning rate of 0.001 and 30 epochs, with a validation accuracy of 95.56% and a testing accuracy of 88.89%. The model demonstrates high confidence in classifying images, particularly for the curl and healthy classes. However, the confusion matrix reveals that the model's performance on the ringspot class remains relatively low due to a high misclassification rate. Overall, the developed system is capable of automatically identifying papaya leaf diseases and has strong potential for implementation as an Android-based application to support early detection and decision-making in plant care.